(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Bio-fertilizer has increased the yield element of wheat significantly. Results from the present study indicated that the yield and growth of wheat; have been affected by inoculation with Azotobacter; as these Bio-fertilizers can fix soil nitrogen. Seed invested with Azotobacter has salutary goods in the soil and also increases the growth and yield of wheat by 5.30%. As a result, Bio-fertilizers can be recommended for the sake of achieving the loftiest quality product. The traits plant height, plant weight could be used for selection of Better yield. The compared result indicated that in the combination of Bio-fertilizer + Chemical fertilizer treatment, good yield was recorded.